Alpha-linolenic acid pretreatment alleviates NETs-induced alveolar macrophage pyroptosis by inhibiting pyrin inflammasome activation in a mouse model of sepsis-induced ALI/ARDS - Liu, Chenchen; Zhou, Yu; Tu, Qing; Yao, Liangfang; Li, Jinbao; Yang, Zhongwei (Frontiers in Immunology, 2023)
Background: Neutrophil extracellular traps （NETs） can cause acute lung injury （ALI）/ acute respiratory distress syndrome (ARDS) by inducing macrophage pyroptosis. This study investigated whether alpha-linolenic acid (ALA) can mediate NETs-induced macrophage pyroptosis in ALI/ARDS, and defined the inflammasome involved in this process. Methods: Lung injury was assessed by microscopic examination of lung tissue after hematoxylin and eosin staining, pathology score, and bronchoalveolar lavage fluid (BALF)total protein concentration. The level of NETs in lung tissue was detected by MPO-DNA ELISA. Purified NETs, extracted from peritoneal neutrophils, induced macrophage pyroptosis in vitro. Expression of pyroptosis-related proteins (Cl-caspase-1, Cl-GSDMD, ASC) and IL-1β in the lung tissue and bone marrow-derived macrophages (BMDMs) were determined by Western Blot or ELISA. Specks of Pyrin/ASC were examined by confocal immunofluorescence microscopy. Mefv(Pyrin)-/- mice were used to study the role of Pyrin in the process of NETs-induced macrophage pyroptosis. Results: ALA alleviated LPS-induced lung injury. ALA reduced the level of NETs, pyroptosis-related proteins(Cl-caspase-1, Cl-GSDMD, ASC), and IL-1β in the lung tissue of sepsis mice. In vitro， NETs increased the expression of pyroptosis-related proteins (Cl-caspase-1, Cl-GSDMD, ASC) and IL-1βsignificantly in BMDMs. Pyrin protein was found to be higher and form the inflammasome with ASC in NETs challenged-BMDMs. Mefv(Pyrin) gene knockout completely restored the NETs-enhanced expression of pyroptosis-related proteins (Cl-caspase-1, Cl-GSDMD, ASC) and IL-1β. ALA suppresses all the NETs-induced changes as mentioned above. Conclusion: Our study is the first to demonstrate Pyrin inflammasome driving NETs-induced macrophage pyroptosis, and ALA may reduce ALI/ARDS by inhibiting the activation of the Pyrin inflammasome-driven macrophage pyroptosis.